Managing energy security : an all hazards approach to critical infrastructure - Burns, Maria G. (Routledge, 2019)
"This interdisciplinary book is written for government and industry professionals who need a comprehensive, accessible guide to modern energy security. Introducing the ten predominant energy types, both renewable and non-renewable, the book illustrates the modern energy landscape from a geopolitical, commercial, economic and technological perspective. Energy is presented as the powerhouse of global economic activities. To ensure the uninterrupted supply of energy, nations, industries and consumers need to have options. Efficient energy security planning ensures that when a primary energy source is depleted, compromised or interrupted, an alternative energy source must be readily available. For this reason, the foundations of energy security are built upon the five pillars of Sustainability, Independence, Efficiency, Affordability and Accessibility. The numerous case studies presented in this book demonstrate that energy security may be compromised in the absence of one out of these five ingredients. The book also entertains the Triple-E notion of Energy Efficiency, Environmental integrity and Economies of scale, used by governments and corporations for energy optimization. One of the key strengths of the book is its ability effectively to cover various scientific disciplines, and several energy types, while remaining comprehensible. This book will be of much interest to security or logistics professionals, economists and engineers, as well as policymakers"--